Type 2 Diabetes Mellitus Related to Decreased Peripheral and Respiratory Muscle Strength in Sarcopenic Thai Elderly - Yuenyongchaiwat, Kornanong; Boonsinsukh, Rumpa (Current Aging Science, 2021)
Background: Age is related to a decline in muscle mass and physical function in both respiratory and peripheral muscle strength, which could lead to mobility and mortality. In addition, older people have suffered from one or multiple chronic conditions in particular in type 2 Diabetes Mellitus (type 2 DM). However, a few studies have reported the relationship between sarcopenic elderly and respiratory and peripheral muscle strengths in type 2DM. Objective: To explore the prevalence of sarcopenia in type 2 DM elderly people among community- dwelling patients and the relationships with peripheral and respiratory muscle loss in sarcopenic type 2 DM older patients. Methods: A total of 330 older individuals were recruited from community-dwelling centers. Respiratory muscle and quadriceps muscle were assessed. According to the defined criteria for sarcopenia (defined by Asian Working Group for Sarcopenia), muscle mass, gait speed (six-meter walk test), and handgrip strength were examined. Results: Of 330 elderly people, 82 volunteers had a history of type 2 DM. Participants with type 2DM had a risk for sarcopenia (odds ratio= 2.324, 95% CI=1.251-4.317). The prevalence of sarcopenia was 25.61% among older participants with type 2 DM. In addition, decreased respiratory muscle strength and quadriceps muscle strength were observed in type 2 DM with sarcopenia compared to type 2 DM with non-sarcopenia. These relationships also remained after controlling for age and sex. Conclusion: Sarcopenia in type 2 DM leads to a decrease in respiratory muscle and peripheral muscle strength.
Keywords: elderly people